2021
DOI: 10.1186/s12903-021-01639-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and age-related differences in the width of attached gingiva and clinical crown length in anterior teeth

Abstract: Background The anatomical features of the gingiva and the clinical crowns and their interrelation, especially in aesthetically and functionally demanding areas, are important in complex dental or implant-retained prosthetic rehabilitations. This observational cross-sectional study was designed to evaluate gender- and age-related differences in the width of attached gingiva (WAG), the clinical crown length (CCL), and their interrelation in the anterior teeth to determine the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…(Table 3) These results were similar with the studies done by Chandulal et al [31], Shaju Jacob P, Zade RM [15], Pradhan et al [26] and Alhajj et al [34]. But in the research by Kolte et al [12], D Rouck et al [35] and Jennes et al [33] where female had less WAG.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…(Table 3) These results were similar with the studies done by Chandulal et al [31], Shaju Jacob P, Zade RM [15], Pradhan et al [26] and Alhajj et al [34]. But in the research by Kolte et al [12], D Rouck et al [35] and Jennes et al [33] where female had less WAG.…”
Section: Resultssupporting
confidence: 87%
“…In this study, participants were categorized into three age groups, and the WAG was measured and compared among these groups. The statistically signi cant difference in the average WAG among the three age groups was noticed (p-value < 0.001 [33] suggested an increase in the WAG with age, while Adesola et al [27] observed no association between the WAG and age. In a study done by P Shaju Jacob & RM Zade [15] in Indian population, the maximum WAG was in middle years age group and lowest in older years age group.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have reported that the thinnest gingiva was found in canines among the maxillary anterior teeth [ 16 17 ]. There are conflicting results regarding the influence of sex on gingival phenotype [ 16 23 31 32 ]. In our study, we observed no differences between female and male participants, which is in line with some previous studies [ 16 23 ] but contradicts others [ 31 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various methods for measuring PP components have been documented, encompassing histological measurements, clinical examinations [ 19 ] and digital assessment [ 20 , 21 ]. Previous studies have demonstrated that digital assessment using CBCT imaging was effective and noninvasive to characterize the phenotypic features of the periodontium compared with clinical methods and histologic assessments [ 22 26 ].…”
Section: Introductionmentioning
confidence: 99%